Freezing Capture of Polymorphic Aggregates of Bolaamphiphilic L‐Valine‐Based Molecular Hydrogelators. Issue 19 (26th March 2014) - Nebot, Vicent J.; Díaz‐Oltra, Santiago; Smets, Johan; Fernández Prieto, Susana; Miravet, Juan F.; Escuder, Beatriu
Abstract Nanostructured xerogels have been prepared by the freeze‐drying of hydrogels and aggregates formed by bolaamphiphilic L‐valine derivatives after aging under different environmental conditions. A wide variety of shapes and sizes has been achieved by a simple methodology. These nanostructures have been studied by SEM and WAXD and a dramatic influence of structural flexibility on the kinetics of aggregation has been observed. Such flexibility and a modulation of the hydrophobic effect have shown a profound influence in the packing of these compounds and revealed a high degree of polymorphism.